PEMANFAATAN SISA BESI (REUSE) DI BENGKEL PRODUKSI SMK NEGERI 4 DUMAI - Melliana, Melliana; Azmi, Azmi; Mesra, Trisna; Fitra, Fitra; Arif, M. (Komunitas Manajemen Kompetitif, 2023)
State Vocational High School 4 Dumai is one of the Technology-based Vocational Vocational Schools. SMK Negeri 4 Dumai is an integrated SMK since it was opened in 2007 with the Agriculture and Technology group which is very supportive of realizing Dumai City as a service and industrial city as well as a gateway for agricultural product exports. SMK N 4 Dumai is a school that is required to have skills after completing studies so that many workshop activities are carried out. In this case, a lot of leftovers or scrap are not utilized and just thrown away. Therefore the Dumai College of Technology will provide skills and skills, namely 1) utilizing leftover iron that is not used, 2) designing and making useful tools Keywords: Students of SMK Negeri 4 , Utilization of Remaining Iron, Designing and making tools